2011
DOI: 10.1007/s00210-011-0675-1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo bladder selectivity of imidafenacin, a novel antimuscarinic agent, assessed by using an effectiveness index for bladder capacity in rats

Abstract: Imidafenacin (KRP-197) is a novel antimuscarinic agent for overactive bladder treatment. The inhibitory effect of imidafenacin on detrusor contraction has been adopted for assessing their bladder selectivity, but this is becoming less convincing as an effectiveness index. We, therefore, reevaluated the bladder selectivity of imidafenacin and other antimuscarinics using their effects on the bladder capacity as an effectiveness index. Bladder capacity was measured by intermittent cystometry in urethane-anestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…In addition, because imidafenacin has the highest relative potency (8.8), calculated as the ID 50 of salivary secretion divided by the ID 30 of distention-induced rhythmic bladder contraction in conscious rats, among propiverine (0.9), tolterodine (5.0), oxybutynin (1.4), and darifenacin (1.4), the drug has organ selectivity for the bladder over the salivary gland 9. Yamazaki et al reported that the relative bladder selectivity of imidafenacin, solifenacin, and tolterodine was 15-fold, 1.7-fold, and, 2.5-fold higher than for the salivary gland; 150-fold, 1.9-fold, and 9.2-fold higher than for the colon; and 50-fold, 12-fold, and 4.6-fold higher than for the heart, respectively, compared with propiverine in a rat study 13. Pharmacokinetic data have demonstrated that imidafenacin administered orally distributes predominantly to the bladder and exerts a more selective and longer-lasting effect on the bladder than on other tissues such as the submaxillary gland, colon, and brain 14.…”
Section: Pharmacological Characteristics Of Imidafenacinmentioning
confidence: 80%
“…In addition, because imidafenacin has the highest relative potency (8.8), calculated as the ID 50 of salivary secretion divided by the ID 30 of distention-induced rhythmic bladder contraction in conscious rats, among propiverine (0.9), tolterodine (5.0), oxybutynin (1.4), and darifenacin (1.4), the drug has organ selectivity for the bladder over the salivary gland 9. Yamazaki et al reported that the relative bladder selectivity of imidafenacin, solifenacin, and tolterodine was 15-fold, 1.7-fold, and, 2.5-fold higher than for the salivary gland; 150-fold, 1.9-fold, and 9.2-fold higher than for the colon; and 50-fold, 12-fold, and 4.6-fold higher than for the heart, respectively, compared with propiverine in a rat study 13. Pharmacokinetic data have demonstrated that imidafenacin administered orally distributes predominantly to the bladder and exerts a more selective and longer-lasting effect on the bladder than on other tissues such as the submaxillary gland, colon, and brain 14.…”
Section: Pharmacological Characteristics Of Imidafenacinmentioning
confidence: 80%
“…Imidafenacin did not cause urinary retention at the dose of 0.2 mg/day, probably because it has a shorter half-life (2.9 hours) and lower accumulation than other anticholinergic drugs. The second possibility is that imidafenacin is less likely to cause urinary retention or to increase the PVR because it may act more specifically on bladder afferent pathways, 27,28 in contrast to drugs acting on the detrusor muscle, which is involved in urinary retention and related to an increase in the PVR.…”
Section: Commentmentioning
confidence: 99%
“…For example, there is an interaction between muscarinic and β-adrenergic systems in the bladder (Witte et al 2011), which may be important pathophysiologically when acetylcholine is released non-neuronally during the storage phase but also therapeutically if a combination treatment of muscarinic antagonists and β-adrenergic agonists is being considered. In this regard, we are still trying to understand why some muscarinic antagonists exhibit a certain degree of bladder selectivity (Yamazaki et al 2011), and it is largely unknown whether a similar phenomenon exists for β 3 -adrenoceptor agonists. Moreover, it is well established that the function of the systemic renin-angiotensin system is in part regulated by β-adrenoceptors, in humans β 1 -adrenoceptors, but a local renin-angiotensin system also exists in the urogenital tract (Comiter 2012).…”
Section: Perspectivementioning
confidence: 99%